water isotopic data for the Dumont d'Urville station, Antarctica, 1 minute resolution, summer season 2016-2017 - Breant, Camille; Leroy-Dos Santos, Christophe; Landais, Amaelle (Zenodo, 2021)
Location: Dumont d'Urville (66°39′46″S140°0′07″E) 4 columns for the raw data - Date-time UTC (hour:minute) - mixing ratio (ppmv) - d18O (permil) - dD (permil) 5 columns for the corrected data - Date - time UTC (hour:minute) - mixing ratio (ppmv) - d18O (permil) - dD (permil) - d-excess (permil) Project COMBINISO